In Vitro Study of Mebendazole (Anthelmintic drug) Effects on the Aspartate Aminotransferase (AST) Enzyme Activity of Hydatid Cyst Parasite - Naderloo, Zahra; Farahnak, Ali; Golestani, Abolfasl; Eshraghian, Mohamad Reza; Molaei Rad, Mohamad Bagher (Archives of Advances in Biosciences, 2016)
Hydatid disease is caused by the larva of Echinococcus granulosus parasite. Mebendazole (MBZ) is used as an alternative choice for the treatment of the disease. Aspartate aminotransferase (AST) is an essential enzyme in amino acid metabolism. The aim of the present study is to evaluate the effect of MBZ on AST activity of hydatid cyst parasite in order to detect enzymatic parameter for drug efficiency. In the present study, AST activity was estimated in the extracts of untreated parasite (hydatid cyst protoscolices) and treated samples by MBZ (100 µg final concentration). Samples’ protein quantity and quality were detected by Bradford and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) methods respectively. For the purpose of determining the significant difference between the two independent samples, t-test was conducted. The values of the assayed AST specific activities of treated and untreated parasite samples were measured as 0.18 and 1.53U/ml/mg protein respectively. The difference between AST activities mean values of the two groups proved to be significant (P<0.05). SDS-PAGE demonstrated protein band of 50 kDa for AST enzyme. Considering the effect of the MBZ drug on AST activity in parasite, it can be concluded that this enzyme is useful for improving the drug efficiency.